The conference on prospects in modern acoustics education and development (How to teach acoustics?) - ŚLIWIŃSKI, A.; LINDE, B. (Archives of Acoustics, 1985)
The aim of the Conference is presentation, discussion and a wide exchange of experience in teaching acoustics in many different world centres which have elaborated programmes and methods in various specializations and in different relations to the educational disciplines in various schools (universities, technical universities etc.) as well as to show what the proper and up to date acoustics ought to be taken into account in the basic, intermediate and advanced courses in physics.